Pengaruh Kesadaran Lingkungan, Digitalisasi Akuntansi, Dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan Pada Lembaga Perkreditan Desa (Lpd) Di Kecamatan Ubud - Ni Putu Intan Melani; Ida Ayu Surasmi (Lembaga Penelitian, Universitas Warmadewa, 2025)
This study aims to analyze the influence of accounting understanding, accounting digitalization, and human resource competency on the quality of financial reports at Village Credit Institutions in Ubud District. The approach used in this study is quantitative with a population consisting of 32 Village Credit Institutions in Ubud District. The sampling technique applied is the saturated sampling technique (census), which aims to minimize errors in data collection, so that the number of samples in this study covers all Village Credit Institutions in the area. The unit of analysis in this study is the organization represented by the head of each Village Credit Institution. Data were collected using a questionnaire and analyzed using multiple linear regression methods. The results of the study indicate that accounting understanding, accounting digitalization, and human resource competency have a significant positive effect on improving the quality of financial reports at Village Credit Institutions in Ubud District.